Sexo na propaganda: da sedução ao desejo de consumo - Costa, Patricia Martins (2006)
Inside the proposal to examine the fundamental role of sexual appeal in advertising, to make of its objects, desire objects of consumers, we cany through an analytical study whose principIe was the semiotic-peirceana theory, in set with the psychoanalysis-Iacaniana theory. From the hypothesis of that an unconscious desire exists that, by means of identifications, determines the desire for the enunciated object, being the advertising only representative of Other, examines the seduction artifices in the advertisings, special, the magazine advertisiment, that they produce make-desiring of consumer. Descriptive and analytical studies had been IDade, elaborated inside of concentration area Sign and Significance in Medias, whose corpus was constituted of advertisiment with appeals sexual, placed in VIP and CLAUDIAmagazines, in period between October and December of2004, and served ofcomment to constitute the analyzed sample. The selection criterion of the sample was given for the identification of sexual appeals in messages. Signs that represent feminilidade and masculinidade had been identified, besides having been possible the revelation of parts of these signs, the foundation, object and, mainly, the some interpretative levels that go of the identification to the consumption. The semiotic analysis of advertisiment opened perspective of understanding of the alienation of citizen to capitalist speech, which stops constituting it, the advertising uses, beyond competent knowing, but, above oí everything, the sexuality in arder to support the consumer desire, since it is accurately this (the desire) that it nourishes the capitalist system contemporary